Persuasion, Justice and Democracy in Plato’s Crito - Liebersohn, Yosef Z. (Peitho. Examina Antiqua, 2015)
Speeches and persuasion dominate Plato’s Crito. This paper, paying particular attention to the final passage in the dialogue, shows that the focus on speeches, persuasion and allusions to many other elements of rhetoric is an integral part of Plato’s severe criticism of democracy, one of the main points of the Crito. Speeches allow members of a democracy – represented in our dialogue by Crito – firstly to break the law for self-interested reasons while considering themselves still to be law-abiding citizens, and secondly to feel that they are in a tolerant society preferring logos/persuasive speech above bia/compulsion. Socrates counters Crito’s speeches with speeches of his own, not only to defeat him at his own game, but also to make him aware how dangerous the game is. Real knowledge is preferable to speeches, but a democracy without speeches and rhetoric is doomed.